ORGANIZING THE PRODUCTION OF LOCAL GRAVEL PRODUCING SMALL ENTERPRISES IN MOUNTAINS AND RIVERSIDES. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article refers to a solid building material formed by weathering of rocks. As it appears, the benefits of processing river, sea, lake, mountain and cliff rocks, as well as local gravel development, are covered